A Survey on Optical Coherence Tomography—Technology and Application - Ali Mokhtari; Bogdan Mihai Maris; Paolo Fiorini (Bioengineering)
This paper reviews the main research on Optical Coherence Tomography (OCT), focusing on the progress and advancements made by researchers over the past three decades in its methods and medical imaging applications. By analyzing existing studies and developments, this review aims to provide a foundation for future research in the field.